2002
DOI: 10.1074/jbc.m204514200
|View full text |Cite
|
Sign up to set email alerts
|

CH···O Hydrogen Bonds at Protein-Protein Interfaces

Abstract: For the first time, a statistical potential has been developed to quantitatively describe the CH⅐⅐⅐O hydrogen bonding interaction at the protein-protein interface. The calculated energies of the CH⅐⅐⅐O pair interaction show a favorable valley at ϳ3.3 Å, exhibiting a feature typical of an H-bond and similar to the ab initio quantum calculation result (Scheiner, S., Kar, T., and Gu, Y. (2001) J. Biol. Chem. 276, 9832-9837). The potentials have been applied to a set of 469 protein-protein complexes to calculate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
168
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(182 citation statements)
references
References 59 publications
10
168
1
2
Order By: Relevance
“…The distance and angle are compatible with the formation of a strong hydrogen bond, i.e., z1.3 kcal mol À1 (Jiang and Lai 2002).…”
Section: Degeneracy In the Genetic Code And Interpretation Of Lagerkvmentioning
confidence: 62%
See 1 more Smart Citation
“…The distance and angle are compatible with the formation of a strong hydrogen bond, i.e., z1.3 kcal mol À1 (Jiang and Lai 2002).…”
Section: Degeneracy In the Genetic Code And Interpretation Of Lagerkvmentioning
confidence: 62%
“…The distance of 3.5 Å estimated from MD simulations is compatible with a hydrogen bond of z0.4 kcal mol À1 (Jiang and Lai 2002). Based on this analysis, the third parameter is defined as follows: We credit U33-N35 with S (''strong'') when N35 is a purine and with W (''weak'') when N35 is a pyrimidine.…”
Section: Degeneracy In the Genetic Code And Interpretation Of Lagerkvmentioning
confidence: 99%
“…34,35 The above mentioned interactions have been parameterized in the CHARMM force field. 36,37 The parameter sets of the CHARMM force field were confirmed to reproduce the binding mode with excellent agreement to the ab initio calculation. In Figure 4C and D, the hydroxyl oxygens of the Ser66 and Ser76 interact with the proton at the edge of the benzene ring.…”
Section: Interactions In Fab-fab-on Orientationmentioning
confidence: 84%
“…Importantly, we showed that FGF14 Y158A or FGF14 V160A alone are not sufficient to disrupt the FGF14:FGF14 dimer formation. In the FGF14:FGF14 dimer homology model, Tyr-158 directly interacts with Val-208 of the neighboring monomer via hydrogen bonding (71). Replacing Tyr-158 with Ala is not sufficient to interfere structurally with the dimer, but if combined with V160A the stability of the ␤-9 strand might be weakened and monomer affinity reduced.…”
Section: Discussionmentioning
confidence: 99%